A REVIEW DESIGN AND ANALYSIS OF BUMPER BEAM SYSTEM IN LOW SPEED FRONTAL IMPACT - MR.CHUMBHALE SHARAD; PROF.AMOL B. GAIKWAD; PROF.AMOL N. PATIL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Bumpers are structural components installed to reduce physical damage to the front and rear ends of a light/heavy motor vehicle from low-speed collisions. Damage and protection assessments are the commonly used design criteria in bumper design. For damage assessment, the relative displacements representing stiffness performance are examined and crash test will be done. The purpose of a crash analysis is to see how the car will behave in a frontal or rear collision. In this study impacts and collisions involving a car bumper beam model are simulated and analyzed using Ls-Dyna software. The bumper should support the mechanical components and the body. It must also withstand static and dynamic loads without undue deflection or distortion. The given model is tested under frontal collision conditions and the resultant deformation and von-Misses stresses are determined. The crash analysis simulation and results can be used to assess both the crashworthiness of current bumper and to investigate the ways to improve the design. Different cross section designs used to determine the performance of the bumper beam in crash test. The comparison of baseline design (C-section) with modified cross section designs of bumper beam are presented in the study. The suitable cross section is then suggested to improve the stiffness and crashworthiness of the beam. This type of study methods are an integral part of the design cycle and can reduce the need for costly destructive testing program.